[Retracted] Transcatheter closure of perimembranous and muscular ventricular septal defects: Short - term and Mid - term outcomes - Ho, Anh Binh; Le Van Duy, Nguyen Ngoc Minh Chau, (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2020)
The article is retracted on the author request